Implementation of Hidden Curriculum in the Formation of Religious Character (Multi-Case Study at SMA Muhammadiyah 1 and SMA Negeri 1 Gresik) - Amirudin, Noor; sutiah, Sutiah; marno, Marno; Supriyatno, Triyo (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The formation of religious character is the key to the success of educational institutions in producing graduates with integrity in the midst of global challenges. This success is not only determined by the formal curriculum, but also the implementation of a *hidden curriculum* that includes values, norms, and good practices in the school environment. This study aims to analyze the implementation model of *hidden curriculum* in the formation of religious character through a multi-case qualitative study with the Miles and Huberman analysis approach. The results of the study show three main findings. First, the concept of "Interconnective-Habitualization of Character" (CPI) which integrates religious values, Pancasila, and national culture holistically in religion-based schools to form a generation of ulama-intellectuals. Meanwhile, in public schools, the *hidden curriculum* is more adaptive, emphasizing the values of honesty, discipline, and tolerance in a plural environment. Second, the implementation is carried out through three channels: formal in Islamic Religious Education, boarding school culture for habituation of religious values, and extracurricular activities as a stimulus for the application of these values. Approaches such as example, habituation, advice, punishment, and technology support implementation. Third, the implication is to increase the religiosity of students, such as worship discipline and involvement in religious activities. This study formulates the "Interconnected-Hidden Curriculum in The Formation of Religious Character" (I-HC) model, which integrates religious education to strengthen the holistic image in faith-based schools and create an inclusive environment in public schools. This model is relevant in building religious characters with integrity in diverse social contexts.